PENENTUAN JARAK TANAM OPTIMAL ANTAR RUMPUN BIBIT PADA METODE VERTIKULTUR RUMPUT LAUT - Petrus R Pong-Masak; Nelly H Sarira (Universitas Gadjah Mada, 2018)
Kappaphycus alvarezii cultivation by the verticulture method has been introduced since 2013. However, scientific studies on some technical aspects are still needed to improve the quality, quantity, and continuity of production and utilization of area in a maximum and productive manner. One of them is the planting distance between seed clumps. The purpose of this study was to determine the optimal planting distance between seed clumps on seaweed verticulture method. Seaweed was cultured using a 10x10 m2 floating raft containing 36 vertical nets of 5x2 m2/net. Seaweed seeds with an initial weight of 50 g were tied to a vertical net with a distance between knot on the verticulture net of 15 cm, 25 cm, and 35 cm. Seaweed cultivation was done for 3 cycles (1 cycle = 45 days) continuously in the cycle of planting season. The experimental units were prepared with Completely Randomized Design (RAL) with 3 replications. The results showed that daily growth rate (DGR) and carrageenan content of seaweed planted with a distance of 15 cm, 25 cm, and 35 cm between clumps were not significantly different (P>0.05). However, it is recommended to apply 25 cm distance between seed clumps in the verticulture method.